Stochastic analyses for managing risk of delay in Duri oil construction projects, Indonesia. Issue 4 (12th March 2022) - Sandhyavitri, Ari
Abstract: This article objective was to identify, assess, simulate, and mitigate risks of delay for the construction of new pressure maintenance (NPM) project located in Duri, Indonesia, based on the combination of stochastic and sensitivity analyses. These both analyses methods are not new but relatively unique to be applied in the area of oil industry especially in Indonesia in generating specific result findings. There were identified 16 major activities are sensitive causing the construction delay. Five significant risks such as; delay in procuring labors, material, and equipment, as well as changes in design and specifications, contributed to the project delay. Based on the stochastic risk analyses, it was identified that an 80% probability of the project would delay for 48 working days. These risks were classified as a high-risk project (delay > 20% from the initial construction project schedule). After conducting risk simulation and risk mitigation measures there were 80% probabilities for reducing the construction delay up to 52.08%. The application of these methods and 6 stages in managing risks would be as an important reference for the oil industry stakeholders in the identification, assessing, and mitigating any possible delays and risks during the construction phase systematically.